2019
DOI: 10.1557/jmr.2019.129
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, surface modification, and applications of magnetic iron oxide nanoparticles

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 79 publications
0
33
0
Order By: Relevance
“…Moreover, they were investigated as carriers for active agents for drug targeting [6]. In the last few decades, several studies showed the development of preparations containing IOMNP to be used for in vitro separation, tissue repair, cellular therapy, magnetic separation, magnetic resonance imaging, as spoilers for magnetic resonance spectroscopy, in drug delivery, hyperthermia, sensors for metabolites, and other biomolecules [6,11,12,16,18,30,[32][33][34][35].…”
Section: Iron Oxides and Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, they were investigated as carriers for active agents for drug targeting [6]. In the last few decades, several studies showed the development of preparations containing IOMNP to be used for in vitro separation, tissue repair, cellular therapy, magnetic separation, magnetic resonance imaging, as spoilers for magnetic resonance spectroscopy, in drug delivery, hyperthermia, sensors for metabolites, and other biomolecules [6,11,12,16,18,30,[32][33][34][35].…”
Section: Iron Oxides and Nanoparticlesmentioning
confidence: 99%
“…These nanoparticles possess very important characteristics, such as superparamagnetism, size, and the possibility of receiving a biocompatible coating. Therefore, ongoing researches are focused on reducing drug concentration, toxicity, and other side effects, and improving the therapy [6,18,21,32].…”
Section: Pharmaceutical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic nanoparticles (NPs) are one of the most fascinating nanomaterials with versatile applications, particularly in magnetic data storage, magnetic resonance imaging, magnetic uids, biotechnology/biomedicine, high performance inductors, catalysis and environmental remediation. [2][3][4] The environmental water pollution caused by inorganics (metal ions), and synthetic organic compounds or their degradation products, such as phenols, organochlorines, polycyclic aromatic hydrocarbon, pesticides, polychlorinated biphenyl, polymers and synthetic dyes, is a great challenge of the modern world due to their persistent nature and ultimate detrimental effects on humans and other living organisms. 5 Synthetic dyes are frequently used (0.7 million tons of about 100 000 different kinds per year) in different industries, including the food, cosmetics, leather, pharmaceutical, paper, plastic and textile industries.…”
Section: Introductionmentioning
confidence: 99%
“…This application of magnetic NPs is associated with their dominant features of reduced size (high surface area), low cost, easy and quick magnetic separation, fast reactivity, high environmental stability and adsorption capacity, easy surface functionalization and low biotoxicity. 2,15 Magnetic nanoparticles of the ferrite group are of current research interest due to their wide range of industrial, biomedical and environmental applications. 3,16,17 Cobalt-ferrite is an efficient member of the ferrite family with dominant properties such as chemical stability, high mechanical stability, wear resistance, high anisotropy and medium saturation magnetization.…”
Section: Introductionmentioning
confidence: 99%